Immunohistochemical and genetic characteristics of lung cancer mimicking organizing pneumonia. (November 2017) - Ichikawa, Tomohiro; Saruwatari, Koichi; Mimaki, Sachiyo; Sugano, Masato; Aokage, Keiju; Kojima, Motohiro; Hishida, Tomoyuki; Fujii, Satoshi; Yoshida, Junji; Kuwata, Takeshi; Ochiai, Atsushi; Suzuki, Kenji; et al.
Highlights: Lung cancer mimicking organizing pneumonia (LCOP) shows significant favorable outcomes. LCOP had fewer tumor-promoting stromal cells in its large central fibrosis area. This feature may account for its favorable prognosis. Abstract: Introduction: Lung cancer mimicking organizing pneumonia (LCOP) is a novel radiological entity of lung adenocarcinoma that could be misdiagnosed as inflammatory lesions. However, the characteristic biological and genetic features of LCOP are not fully clarified. Materials and methods: We used thin-section CT images to select cases of (LCOP) among surgically resected lung adenocarcinoma patients. We compared the clinicopathological characteristics and the immunophenotypes of LCOP (n = 44) and other lepidic-predominant adenocarcinomas (non-LCOP, n = 56). We also analyzed the genomic mutation features of LCOP (n = 4) by whole-exome sequencing (WES). Results: All LCOP lesions were lepidic-predominant invasive adenocarcinoma. Patients with LCOP had significantly superior recurrence-free survival, compared to non-LCOP patients (95.5% and 74.4%; P = 0.006, respectively). Vascular invasion and lymph node metastasis were less frequent in LCOP than in non-LCOP patients (P = 0.001 and P = 0.03, respectively). The cancer cell expression levels of aggressiveness-related molecules, including ezrin, ALDH-1, laminin-5 were similar between LCOP and non-LCOP. On the contrary, the number of tumor promoting stromal cells, i.e., podoplanin-positive cancer-associated fibroblasts and CD204-positive tumor associated macrophages, was significantly lower in LOCP (P = 0.021 and P = 0.037, respectively). WES revealed that ABCB1, DNAH3, MSI2, and SLITRK2 were specifically mutated in LCOP. Conclusions: Our results indicate that LCOP is characterized by fewer tumor-promoting stromal cells, which may contribute to the better prognosis of LCOP patients. Moreover, recognition of specific somatic mutations of LCOP patients may provide information regarding the development and progression of this type of lung cancer.